Bird Composition, Abundance and Diversity across Habitat Types in Shere Hills Reserve, Plateau State, Nigeria (Lafia Journal of Scientific and Industrial Research, 2025)
This study examined bird composition, abundance and diversity in Shere Hills Reserve, Jos Plateau, North Central Nigeria. The region, characterized by a savanna ecosystem interspersed with rocky outcrops and gallery forests, has a mean annual rainfall of 1,260 mm and a temperature range of 19.4°C to 34.5°C. Bird surveys were conducted across 65 points using the point count method, stratified by habitat type: gallery forest, savanna, and rocky outcrops. Observations were made daily between 6:30 a.m. and 10:30 a.m., and species were identified using ‘Birds of Western Africa’ field guide. A total of 6,427 birds representing 142 species and 53 families were recorded. Gallery forests exhibited the highest species composition (121 species), followed by savannas (111 species), and rocky outcrops (108 species). Notable species included Blue-breasted Kingfisher in gallery forests, Chestnut-backed Sparrow Lark in savannas, and Rock-loving Cisticola in rocky habitats. Despite these differences in species composition, bird abundance and diversity did not vary significantly across habitats (F2, 585 = 0.59, p = 0.56). The savanna (1.92 ± 0.03) and gallery forest (1.91 ± 0.03) had slightly higher diversity compared to rocky outcrops (1.87 ± 0.03). The findings underscore the importance of habitat heterogeneity in supporting avian biodiversity in Shere Hills Reserve, with gallery forests and savannas contributing significantly to species richness and diversity.